2009
DOI: 10.1017/s1751731109004777
|View full text |Cite
|
Sign up to set email alerts
|

Physiological variables of horses after road transport

Abstract: In order to investigate the effects of short road transport stress on total and free iodothyronines, body weight (BW), rectal temperature and heart rate (HR) changes, 126 healthy stallions were studied in basal conditions, before and after transport. A total of 60 Thoroughbred and 66 crossbred stallions aged 4 to 15 years with previous travelling experience were transported by road in a commercial trailer for a period of about 3 to 4 h (distance under 300 km). Blood samples and functional variables were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…In our study, the heart rate and respiratory rate were significantly increased ( P  = 0.0169 and 0.0155 respectively), while the body temperature and CRT were not changed during transport or during the post-transport period. These observations are consistent with results of other authors, who studied the impact of road transport on basic clinical signs [17,18]. The respiration rate was increased in horses in response to a 12 hour transport period and the heart rate was increased in horses after a 24 h transport [7].…”
Section: Resultssupporting
confidence: 91%
“…In our study, the heart rate and respiratory rate were significantly increased ( P  = 0.0169 and 0.0155 respectively), while the body temperature and CRT were not changed during transport or during the post-transport period. These observations are consistent with results of other authors, who studied the impact of road transport on basic clinical signs [17,18]. The respiration rate was increased in horses in response to a 12 hour transport period and the heart rate was increased in horses after a 24 h transport [7].…”
Section: Resultssupporting
confidence: 91%
“…The results obtained showed that transport and show jumping competition differently influenced the thyroid responses of trained sport horses to physiological and psychological stress, according to the individual experimental sessions. The increase of total and free iodothyronines after transport (session T0) confirmed previous data observed in sport horses after road transport, underlining the metabolic active effects of thyroid hormones in response to stressful stimuli previously described in sport horses [3] and in Thoroughbred and Crossbred stallions [4] after road transport of 100 and 300 km, respectively. The greatest release of T 3 and T 4 after transport could represent the final result of preferential release of T 3 from the thyroid gland and/or a probably increase of peripheral monodeiodination of T 4 , although a synchronous release of T 4 was observed.…”
Section: Discussionsupporting
confidence: 88%
“…Testing procedure was based on enzyme-linked immunosorbent assay/competition to polyclonal biotinylated ovine iodothyronine antibodies using streptavidin technology. Limits of detection were 0.24 nmol/L for T 3 , 5.79 nmol/L for T 4 , 0.15 pmol/L for fT 3 , and 1.3 pmol/L for fT 4 . Intra-and inter-assay coefficients of variation were 7.3% and 11.4% for T 3 , 2.3% and 5.7% for T 4 , 4.2% and 11.9% for fT 3 , 6.6% and 9.6% for fT 4 , respectively.…”
Section: Hormone Analysesmentioning
confidence: 95%
See 1 more Smart Citation
“…Schmidt et al (2010) reported high HR values (higher than basal HR values) up to 6 h after a journey duration of 8 and 3.5 h. In our study, horses arrived at the competition centre 1 day before the jumping exercise. Fazio et al (2009) suggested a cumulative effect on an individual horses's HR due to novel environments experienced during transport. Taking into consideration that the animals used in this study were young (4 to 6 years old) and thus more inexperienced, the stress related to 'journey duration' together with the stress related to the competition event, could increase this cumulative effect, leading to a decrease in the horse's physical resistance and workload and, hence, its performance ability.…”
Section: Discussionmentioning
confidence: 99%